Accelerated Permafrost Thaw Linked to Rising River Temperature and Widening Channels - Yi Zhao; Dongfeng Li (Geophysical Research Letters)
Abstract River‐controlled permafrost dynamics are crucial for sediment transport, infrastructure stability, and carbon cycle, yet are not well understood under climate change. Leveraging remotely sensed datasets, in‐situ hydrological observations, and physics‐based models, we reveal overall warming and widening rivers across the Tibetan Plateau in recent decades, driving accelerated sub‐river permafrost thaw. River temperature of a representative section (Tuotuohe River) on the central Tibetan Plateau, has increased notably (0.39°C/decade) from 1985 to 2017, facilitating heat transfer into the underlying permafrost via both convection and conduction. Consequently, the permafrost beneath rivers warms faster (0.37°C–0.66°C/decade) and has a ∼0.5 m thicker active layer than non‐inundated permafrost (0.17°C–0.49°C/decade). With increasing river discharge, the inundated area expands laterally along the riverbed (16.4 m/decade), further accelerating permafrost thaw for previously non‐inundated bars. Under future warmer and wetter climate, the anticipated intensification of sub‐river permafrost degradation will pose risks to riverine infrastructure and amplify permafrost carbon release.